An overview on the risk associated with cryptocurrency and its applications (Journal of Pure and Applied Sciences (Science Forum), 2026)
The global economic system is amazingly complicated. At its fabric, this superficially complex system disintegrates into a set of few rules that sum up how humans trade their notions of value. The Internet has changed the entire game for the age-old systems, so it is no surprise that it has caused immense disruption to the financial system too. It does not seem like technology is going to stop its disruption to financial systems anytime soon. Blockchain eliminates the traditional role of a middleman which is required in financial institutions like banks that are supervised by authorities. An important feature of blockchain is that it is public; everyone can see it because it acts as a public ledger which is updated after every transaction. Every transaction becomes a block which is then checked by others’ computer and approved. This paper examines cryptocurrency adoption factors, the challenges, the risk associated with it, Cryptocurrency Anti-Money Laundering Red Flags and the Nigeria economy.